Effects of whey-enriched drinking water on fattening merino lamb growth, hemogram, inflammation, oxidant and antioxidant parameters - Danyer, E; Bilal, T; Altiner, A; Eseceli, H (Journal of the Hellenic Veterinary Medical Society, 2024)
This study aimed to evaluate the oxidative stress and inflammation status of ad libitum whey consumption as drinking water on fatting Merino lambs (n=24). Lambs were randomly divided into two groups and received ad libitum freshwater or whey enriched water and had clover as roughage and lamb grower feed as concentrate daily. Blood samples were collected before the trial (T1), on the 15th (T2) and 30th (T3) days and analyses were conducted on hemogram, serum antioxidant enzymes (Superoxide dismutase, SOD; Glutathione peroxidase, GSH-Px) inflammation response (C-Reactive Protein, CRP), complement activation, and chemokine marker (complement component 4, C4), lymphocyte activation factor (Interleukin 1 beta, IL-1 β), systemic inflammation cytokine (Tumor necrosis factor-alpha, TNF-α), lipid peroxidation marker (Malondialdehyde, MDA). The rate of hematocrit was found to be higher in the experimental group in T3 (35.55 ± 10.54) compared to the control group (44.50 ± 2.58). The platelet amounts were found to be higher in the whey group in T2 and T3 compared to the control group (p<0.05). In conclusion, with the use of whey protein-enriched drinking water, no significant change was observed in the amounts of TNF-α, SOD, MDA, IL-1β, C4, CRP under these study conditions.